Macroeconomic Policy in New Zealand: From the Great Inflation to the Global Financial Crisis - Bruce White (New Zealand Government, The Treasury, 2013)
This paper surveys the evolution of macroeconomic policy, in the New Zealand context, from the beginning of the end of the Great Inflation of the 1970s/1980s, through to the current recovery from the Great Recession brought on by the Global Financial Crisis. The 30 or so years since the late 1970s is divided into four periods: the run-up to the mid-1984 currency crisis; the period of reform from that point until the early 1990s; the subsequent extended period of non-inflationary growth in the 1990s and into the 2000s (punctuated by the Asian Financial Crisis in 1997/98); and the GFC and the years since. The paper reviews macroeconomic policy and developments across each of these periods in relation to fiscal policy, monetary policy, exchange rate policy and prudential supervision, all of which at various times have been used with macroeconomic objectives in mind. The paper concludes with some observations on where macro policy appears to be headed, suggesting that is towards achieving some re-integration of its individual components.
Keywords: E52; E62; E63; 330; Macroeconomy; fiscal policy; monetary policy; exchange rate policy; macro-prudential policy; prudential supervision